(3JTHjY ef GMJad dJTLjY ef Hg aTds - (3CHhGdHQcGJ eMeO Hf YHO GdLHGQs; (3CHhGdHQcGJ eMeO Hf YHO GdLHGQs
(3ChdgG (B:s
(3GdMeO ddg MeOkG dG JSJbUjg GdeaQOGJ hGdLed CQLhRJj GdeSeGI HJTLjY ef Hg GdaTd SDGdGJge efj Cf CYRRgG HTQM jMbb eG ajgG s
(3BNQgG (B:s
(3aGdQaY GSe hefaj GdNHQ, hbhdg hdG ef SHH LedI MGdjI hGLJdi GaJYd HeYfi Ldi s
(3fSNI JYGhQ YdjgG fGSNGfs
(3hHgG fXGe GdJYbjHIs
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B2 - (3U (B72 s
Keywords: (3GdfMhs